Upaya Penanggulangan Tindak Pidana Terorisme Dalam Perspektif Kriminologi - Nahdhodin, Muhammad; Sudarmanto, Kukuh; Triwati, Ani; Arifin, Zaenal (JURNAL USM LAW REVIEW, 2024)
The study aims to examine attempts to counter-terrorism from a criminological perspective. This research is important given that terrorist crime is a global threat that affects countries and communities, with potentially negative effects, both physically and psychologically. The novelty of this research is in an attempt to counteract terrorist crime with a criminological perspective that uses local "jogo tonggo" wisdom. This research is a sociological jurisprudence.  The results of the research showed efforts to combat terrorist crime from a criminological perspective: character identification and funding, national preparedness, counter-radicalization, deradicalization, and radical anticipation of terrorism in Lapas. Control the fight against terrorism in Java Among other things, there is still a radical Napiter, the rise of gotong royong values, society tolerant of terrorists, legal sanctions of educational institutions, and charity of weak terrorist groups. Overcome the obstacles in combating terrorist crime requires a structured and adaptive strategy to strengthen intelligence networks by improving surveillance technology and enhancing cross-country cooperation for the exchange of information, training, and monitoring of former Napiter through a religious building, tolerance, national insight involving Islamic religious figures, implementation of jogo tonggo programs, acceleration of regional action plans for prevention and combating extremism leading to violence, and economic empowerment..Penelitian ini bertujuan untuk mengkaji upaya penanggulangan tindak pidana terorisme perspektif kriminologi.  Penelitian ini penting mengingat tindak pidana terorisme merupakan ancaman global yang merambah berbagai negara dan masyarakat, dengan potensi dampak yang sangat merugikan, baik secara fisik maupun psikologis. Penelitian ini penting mengingat tindak pidana terorisme merupakan ancaman global yang merambah berbagai negara dan masyarakat, dengan potensi dampak yang sangat merugikan, baik secara fisik maupun psikologis. Kebaruan penelitian ini adalah dalam upaya penanggulangan tindak pidana terorisme dengan perspektif kriminologi yang menggunakan kearifan lokal "jogo tonggo". Penelitian ini merupakan penelitian yuridis sosiologis. Hasil penelitian menunjukkan upaya penanggulangan tindak pidana terorisme perspektif kriminologi: identifikasi karakter dan pendanaan, kesiapsiagaan nasional, kontra radikalisasi, deradikalisasi, antisipasi radikal terorisme di Lapas. Kendalah penanggulangan terorisme di Jawa Tengan antara lain masih adanya Napiter yang radikal, lunturnya nilai gotong royong, masyarakat permisif kepada teroris, sanksi hukum lembaga pendidikan dan amal kelompok teroris lemah. Dalam mengatasi kendala dalam penanggulangan tindak pidana terorisme membutuhkan strategi yang terstruktur dan adaptif memperkuat jaringan intelijen dengan memperbaiki teknologi pengawasan dan meningkatkan kerjasama lintas negara untuk pertukaran informasi, pembinaan dan monitoring mantan Napiter melalui pembinaan agama, toleransi, wawasan kebangsaan melibatkan tokoh agama Islam, implementasi program jogo tonggo, percepatan rencana aksi daerah pencegahan dan penanggulangan ekstremisme yang mengarah pada kekerasan, dan pemberdayaan ekonomi.